Dialogue learning as an innovative pedagogical technology (Actual Problems of Psychology in Educational Institutions, 2018)
The article reveals the essence of innovative pedagogical technologies, highlights the theoretical aspect of dialogue education, describes the technology of its organization in various forms of training in the process of professional training of the future teacher.
Keywords: technology; innovative technology; dialogue; dialogue training